Sistem Pendukung Keputusan bagi Penerima Bantuan Komite Sekolah Menggunakan Metode Topsis - Mardayatmi, Suci; Defit, Sarjon; Nurcahyo, Gunadi Widi (Rektorat Universitas Putra Indonesia YPTK Padang, 2021)
Vocational High School Number 3 Mukomuko was the school that has given assistance for the learners. It was by exempting learners from paying committee charge monthly, it called Bantuan Komite Sekolah (BKS). In order to give motivation for the learners who was unfortunate to keep staying at the school, so it can make the learners to keep going on teaching and learning process (KBM). This research used Topsis method by collecting data for the prospective scholarship learners as many as 20 learners by categorizes were parents’ revenue, the total numbers of duties, the distance of residence, the average score of report and the condition of living environment. The result of try out from 20 learners who was obtain BKS by using Topsis Method showed that there were 18 learners who were significant to obtain scholarship by validity score was 90%. It was be a sample, before Topsis Method was used and the data was reliable after using Topsis Method. The development of supporting decision application system used Topsis Method that was getting in more accurated qualification. Futhermore, this system can help the school in constructing decisions to get the result be more advantageous in determining for the next BKS recipients.